Role of Radiology in Forensic Dentistry - T Chandrasekhar; P Vennila (Wolters Kluwer Medknow Publications, 2011)
Forensic radiology is a specialized area of medical imaging utilizing radiological techniques to assist physicians and pathologists in matter pertaining to the law. Postmortem dental radiographs are the most consistent part of the antemortem records that can be transmitted during the forensic examination procedures. Pathologists regularly use radiographic images during the course of autopsy to assist them in identification of foreign bodies or determination of death. Forensic radiology can be used in suspicious death or murder, in analysis of adverse medical events, solving legal matters, to detect child abuse, drug trafficking, body identification and disease identification. Using the possibilities of radiology, special characteristics of the internal structures of the dentomaxillofacial region can be revealed. We can also detect endodontic treatments, healing extraction sockets, implants or even tooth colored restoration. Therefore, we can give answers to problems dealing with identification procedures, mass disaster and dental age estimation.